Genetic Markers for Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis in the Asian Indian Population: Implications on Prevention - Shanbhag, Swapna S.; Koduri, Madhuri A.; Kannabiran, Chitra; Donthineni, Pragnya R.; Singh, Vivek; Basu, Sayan (Frontiers in Genetics, 2021)
This review attempts to collate all the studies performed in India or comprising of a population originating from India, to find out if there is an association between the HLA (human leucocyte antigen) type of an individual and development of Stevens-Johnson syndrome/toxic epidermal necrolysis (SJS/TEN) subsequent to medication use. The authors performed a PubMed search of all articles published in English from 2009 to 2019 for articles that studied HLA type in patients who developed SJS/TEN after intake of a specific drug in the Asian Indian population or in individuals of Asian Indian origin. The selection criteria were satisfied by a total of eleven studies that reported HLA associations with specific drugs which induced SJS/TEN, mainly anti-epileptic drugs, and cold medicine/non-steroidal anti-inflammatory drugs. These studies involved a small number of patients, and hence there is limited evidence to conclude if these associations can be extrapolated to a larger population of the same ethnicity. Similar multi-centre studies need to be conducted with a larger sample size to confirm these associations. This would have implications in policy making and for understanding the potential of using genetic markers as a screening tool before prescribing a drug to a patient which might make them susceptible to developing a potentially life-threatening disease such as SJS/TEN. This is possibly the only mode of primary prevention for this potentially fatal severe cutaneous adverse drug reaction.